Constraints on the appearance of a maximum in astrophysical S-factor - V.V. Sargsyan (Elsevier, 2022)
For fusion reactions of astrophysical interest, the existence of a maximum of S-factor is revealed within the extended quantum diffusion approach. The available experimental data are well described. The reason and consequences of the existence of the S-factor maximum are explained. An universal formula for the position of the maximum is proposed.